PENGARUH STRUKTUR KEPEMILIKAN DAN STRUKTUR MODAL TERHADAP AGENCY COST - Tyara Dwi Putri (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2017)
The research examines the influence of ownership structure, capital structure, and agencycost on corporate at Indonesian Stock Exchange. Unbalanced panel data is used in this research.Type of ownership is determined by institutional ownership and concentration ownership. Capitalstructure is determined by leverage. Proxy of agency cost is asset utilization and expense ratio. Theresults of this study show that institutional ownership, concentration ownership, and leveragereduces the agency cost significantlyKeywords: institutional ownership, concentration ownership, leverage, agency cost, assetutilization, expense ratio